Decreasing Energy and Water Use in the Meat Industry - Eszes, Ferenc; Fenyvessy, József (Acta Agraria Debreceniensis, 2005)
The technology supervisions are needed from time to time in order to involve the new research results, experience, new technologies and equipments organising principles into the production and to make it cheaper and with less expenditure to increase the profitability and competitiveness. In the course of our investigation we aimed the analysis of the traditional technologies and improving of it. In this article we detail the heat treatment curing process. We applied the principles of experimental design for the determination the main influencing parameters in the processes. Then we made simulations and modelling in seeking for the environmentally better technology programs. We developed a method for measuring the temperature development of products with small diameter using the similarity theory in unit operation. In the course of the analysis of the heat treatment processes we could state that the heat treatment time can be reduced significantly by decreasing the size of the product and choosing the right ratios among the surface heat transfer intensity, ambient temperature and involving the lethality obtained during the cooling phase. The total sparing were about 10-20%. We solved the problem associated with the sensor placement error using a plastic material (metamid). We establish a curve between the real product temperature and plastic rod temperature by which the monitoring of the process became more accurate. We determine the size modification for different product sizes. In case of curing we observed very similar phenomena. For the determination of the diffusion coefficient we adopted the Ball-method not using in this field till today. We could reduce the excess saltiness and loss of NaCl with about 5%.